A tree is nice. - Udry, Janice May.; Simont, Marc. ([New York] Harper, 1956)
Briefly describes the value of a tree.
"Library edition."--Dust jacket.
Keywords: Trees -- Juvenile literature; Trees; Caldecott Medal